Polysaccharides From Abrus cantoniensis Hance Modulate Intestinal Microflora and Improve Intestinal Mucosal Barrier and Liver Oxidative Damage Induced by Heat Stress - Wang, Ying; Sun, Wenjing; Wu, Enyun; Wang, Kaijun; Chen, Xiaogang; Cui, Yao; Zhang, Geyin; Lv, Feifei; Wang, Yuhan; Peng, Xiaomin; Si, Hongbin (Frontiers in Veterinary Science, 2022)
The protective effects of ACP on antioxidant capacity, immune function, HPA axis balance, intestinal mucosal barrier and intestinal microflora in heat stress (HS) induced heat-injured chickens were rarely reported. The purpose of this study was to investigate the protective effects of ACP on heat stress-injured chickens by enhancing antioxidant capacity, immune function, repairing intestinal mucosal barrier, and regulating intestinal f microfloralora. A total of 120 roosters were randomly divided into 5 groups to evaluate the protective effect of ACP on chickens injured by heat stress. The results showed that ACP could increase the body weight and immune organ index of heat-injured chickens, increase the secretion of SOD and Nrf2 in liver and serum, significantly reduce the levels of MDA, HSP70 and Keap1 in liver and serum, and restore the antioxidant level of heat-injured birds. Significantly increased COR is a sign of heat stress. Moreover, HS activated the HPA axis and significantly promoted the secretion of CRH and ACTH, resulted in the disorder of hormone level. ACP can significantly inhibit the secretion of CRH, ACTH and COR, reverse the disorder of hormone levels caused by HS, and make them tend to return to normal levels. ACP can significantly reduce the level of SIgA and IL-6 in serum and ileum, significantly increase the level of IL-10 in serum, and restore the immune function of the body. ACP significantly increased villus height (VH) and crypt depth (CD), increased intestinal wall thickness (IWT) and villus height/crypt depth (VH/CD), intestinal tight junction protein expression levels were improve，which improved intestinal morphology, strengthened intestinal barrier and had a positive effect on protecting intestinal health. The results of high-throughput sequencing of 16S rRNA gene showed that HS led to an increase in the abundance of harmful bacteria and abnormally increased the abundance of intestinal microflora, and ACP restored the HS-induced intestinal microflora imbalance. In conclusion, this study provides a scientific basis for ACP as an antioxidant activity enhancer to reduce liver injury, regulate intestinal microflora and protect intestinal mucosal damage in chickens.